Magnifying endoscopy with narrow-band imaging is more accurate for determination of horizontal extent of early gastric cancers than chromoendoscopy - Asada-Hirayama, Itsuko; Kodashima, Shinya; Sakaguchi, Yoshiki; Ono, Satoshi; Niimi, Keiko; Mochizuki, Satoshi; Tsuji, Yosuke; Minatsuki, Chihiro; Shichijo, Satoki; Matsuzaka, Keisuke; Ushiku, Tetsuo; Fukayama, Masashi; Yamamichi, Nobutake; Fujishiro, Mitsuhiro; Koike, Kazuhiko (Endoscopy International Open, 2016)
Background and study aims: Although magnifying endoscopy with narrow-band imaging (ME-NBI) is reported to be useful for delineating the horizontal extent of early gastric cancers (EGCs), there are few reports which have objectively demonstrated the superiority of ME-NBI over chromoendoscopy with indigo carmine for this purpose. We conducted an exploratory comparison of the diagnostic accuracy of both modalities for the delineation of EGCs using prospectively collected data, and clarified the clinicopathological features related to inaccurate evaluation of the horizontal extent of EGCs.Patients and methods: EGCs were assigned to the oral narrow-band imaging (O-NBI) group or the oral chromoendoscopy (O-CE) group before endoscopic submucosal dissection (ESD). The oral border was observed according to assignment, and the anal border with the other modality. The horizontal extent of the tumor was evaluated by each modality and a marking dot was placed on the visible delineation line. After ESD, the marking dots were identified pathologically and defined as “accurate evaluation” if they were located within 1 mm of the pathological tumor border. We compared the rate of accurate evaluation of ME-NBI and chromoendoscopy, and analyzed the clinicopathological features related to inaccurate evaluation.Results: A total of 113 marking dots evaluated by ME-NBI and 116 evaluated by chromoendoscopy were analyzed. The rate of accurate evaluation by ME-NBI was significantly higher than that by chromoendoscopy (89.4 % vs 75.9 %, P = 0.0071). The EGCs with flat borders and large EGCs were significantly related to inaccurate evaluation using ME-NBI. There were no significant factors related to inaccurate evaluation with chromoendoscopy.Conclusions: The accurate evaluation rate of the horizontal extent of EGCs by ME-NBI is significantly higher than that by chromoendoscopy.Study registration: UMIN000007641